Spatial identity (re)constructed from web-sourced imagery: Comparing expert opinion with quantitative query. Issue 2 (15th May 2017) - Juvancic, Matevz; Verovsek, Spela
Abstract : Purpose: Spatial identity is an important constituent of general cultural identity in that it provides its share of continuity, sustainability, character and inertia. The purpose of this paper is to trace spatial identity's formulation, reflection and perception within the mainstream media. The authors are particularly interested in spatial identity's general aspect, consisting of architectural and other elements that give spatial character to places, making them both common and recognisable at the same time. The proposed spatial identity presence index is one of the indicators through which stakeholders in cultural heritage management could monitor, and even manage, the public perception of built heritage's wider context. Design/methodology/approach: The research seeks wider relevance through the development of new methodology that combines web search services, visual data quantification, and data mining methods, and compares this with expert opinion. The research methodology is showcased and established in terms of the connection between the fundamental work in relation to Slovenian architectural landscapes from the pre-internet era and spatial identity's web reflection as broadcast and collectively co-shaped by the internet-permeated society more than 20 years after the internet's inception. Findings: The findings indicate that results based on expert opinion and results acquired by counting spatial character carrier elements are aligned. Originality/value: The introduced index of web-sourced spatial identity presence measures web-projected spatial characteristics in selected settlements. It is applicable in similar cases where the existing body of work on local spatial identity allows it, and can be used for comparative purposes. It also has social, economic and political connotations.